France : Selected Issues; Labor Market Developments and Wage Moderation in France in the 1990s. (IMF Staff Country Reports; Country Report, 2001)
The growth rate of real hourly wages in France has fallen below the trend growth rate of total factor productivity. The distribution of wage and earnings growth has not been uniform across deciles. A breakdown in employment growth by wage deciles also suggests important composition changes. The development of key labor market variables has been discussed in this note. Microeconometric estimations provide evidence of an outward shift in the relationship between wages and unemployment that is independent of changes in labor demand taxes and unemployment income.